STEM IN ACTION: VIDEO COURSE “ARDUINO IN TINKERCAD - Voronkin, O. S. (Scientific Notes of Junior Academy of Sciences of Ukraine, 2023)
In the context of an integrated approach to education, this paper emphasizes the importance of utilizing video resources as a powerful tool for STEM education. The authors present their experience in creating a series of video lessons aimed at disseminating knowledge on Arduino programming using the TinkerCAD platform. The use of this platform allows individuals to learn programming even when access to physical Arduino boards is limited, which is especially relevant in the face of destructions in Ukraine’s educational infrastructure and mass migration of educational participants. The need for multimedia Ukrainian content on YouTube is stressed as a means to popularize knowledge about methods and techniques of Arduino programming in TinkerCAD among a broad audience, including students of different age groups and educators interested in electronics and STEM education. The content of the video lessons is described, highlighting their significant feature — the hyperlink of TinkerCAD projects. This interactivity enables teachers and students to actively improve their skills and projects while simultaneously watching video lessons, simplifying the learning process. An analysis of the author’s YouTube channel demonstrates substantial interest in this content, both from students of general secondary education institutions of Ukraine and viewers of arious age groups from different countries. This popularity attests to the relevance and importance of the “Arduino in TinkerCAD” video course as a whole. In conclusion, this article will be a valuable instructional resource for educators seeking to implement innovative teaching methods for STEM subjects using Arduino, especially in the face of modern challenges.